Dynamic Compression of a Brittle Spherical Specimen - Nowacki, W.K. (Engineering Transactions, 1994)
The dynamic compression process of a spherical specimen made of a brittle material in the split Hopkinson pressure bar (SHPB) is described. The aim of the present paper is to determine the stress distribution over a spherical surface as a result of passage of a wave carrying compressive stresses. The specimen is treated as a quasi-rigid body, the wave process in the SHPB system being taken into account, however. Solution of such a problem is essential for the description of the disintegrating (crushing) process of rock materials, for instance.